POVERTY AND PROSPERITY VIEWED BY THE VIDZEMES TEACHERS - Mihailova, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
This article analyses the opinions about the difference between poverty and prosperity among the teachers, it seeks to find the border between these phenomena; it summarizes the teachers' ideas of how to diminish poverty and use one's own money effectively in times of prosperity. By using the open ended questionnaire the results of 1 teacher groups from schools of 2 Latvian districts were analyzed. Summarizing the results one can conclude that the interviewed teachers with the word "poverty" and "prosperity" understand material things. Teachers associate money the means of living which is acquired by working and earning. None of the respondents admitted that they would ask for help, look for support and receive the social benefits or would seek for the cause of poverty within themselves in case of experiencing poverty. In case of becoming prosperous the teachers will meet all their needs and then be ready to share with others. Almost all teachers' answers disclosed that they will spend money rather than invest it and make accumulation or accruals. The interviewed teacher did not make any original proposal to resolve poverty issue. The main boundary between poverty and wealth is the amount of money which allows or does not allow meeting their own needs and desires thus ensuring certain way of life or life style. The second boundary is the place of living and appearance. Essential boundary is also emotional comfort or discomfort, a happy relationship or lack of it. It should be noted that this study only shows the trend since a very specific selection of respondents was involved. However, it allows making the assumption that teachers had a healthy attitude towards money and hardly any teacher had a negative attitude towards money or prosperity, however, everybody believed that poverty can be avoided by working and earning money. Thus it is possible to conclude that the teachers of this selection don't hold the "ideology of low-income people".